Relationship between Motivation and Performance of Posyandu Cadres in Stunting Prevention at Lima Ilir Health Center Palembang - Arifin, Jafar; Supriyati, Dina (Universitas Pekalongan, 2024)
Stunting prevention is very important to support Indonesia's golden generation. Monitoring children's health and development through the Integrated Posyandu program is very important for families with young children. Posyandu is an important tool in the community to support efforts to achieve a prosperous society. The success of Posyandu is influenced by the cadres' motivation to carry out their roles and functions. There are many factors that influence the performance of posyandu cadres and what is examined in this study is motivation. This research aims to determine the relationship between motivation and cadre performance. The research design in this study was a correlation descriptive study with a cross sectional approach. The independent variables in this study is motivation, while the dependent variable in this study is the performance of cadres. The population in this study were all cadres in the working area of the Lima Ilir Public Health Center, Palembang City, Sample of this study is 53 cadres. The results showed that cadres motivation has significant relationship with the performance of posyandu cadres (p-value : 0.040). Cadres are expected to increase motivation and performance with carry out their functions, namely by going directly to the house to listen to the community's complaints. And for the leaders of the health center to encourage cadres to maintain and improve their performance with training to cadres and give awards for the achievement of the work that has been done